2022
DOI: 10.3390/jfmk7010016
|View full text |Cite
|
Sign up to set email alerts
|

Is Muscle Architecture Different in Athletes with a Previous Hamstring Strain? A Systematic Review and Meta-Analysis

Abstract: Hamstring strains are a frequent injury in sports and are characterized by a high recurrence rate. The aim of this review was to examine the muscle and tendon architecture in individuals with hamstring injury. A systematic literature search in four databases yielded eleven studies on architecture following injury. Differences in the fascicle length (FL), pennation angle (PA) and muscle size measures (volume, thickness and physiological cross-sectional area) at rest were not significantly different between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…A recent meta-analytic study [26] indicated moderately shorter BFlh fascicle lengths of injured legs of the athletes (effect size = 0.57), which is similar to our present research (effect size = 0.62). Variability of results in the literature might have multifactorial causes including athlete age [47, 78,79], ethnicity [80], sports disciplines [81], rehabilitation process [82][83][84], abd ultrasound measurement methods [17,38].…”
Section: Plos Onesupporting
confidence: 91%
See 4 more Smart Citations
“…A recent meta-analytic study [26] indicated moderately shorter BFlh fascicle lengths of injured legs of the athletes (effect size = 0.57), which is similar to our present research (effect size = 0.62). Variability of results in the literature might have multifactorial causes including athlete age [47, 78,79], ethnicity [80], sports disciplines [81], rehabilitation process [82][83][84], abd ultrasound measurement methods [17,38].…”
Section: Plos Onesupporting
confidence: 91%
“…A previous study [ 26 ] suggested that neural inhibition following the injury [ 24 29 ] and reduced exertion may cause BFlh fascicle shortening at the early phase of rehabilitation [ 22 ]. Together with the former, decreased participation in sports [ 24 ] are a possible underlying mechanism for the shortening of BFlh fascicle lengths after injury.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations